PERCEPTIONS OF RIVERINE PREGNANT WOMEN ON PRENATAL CARE - Alexandre Aguiar Pereira; Fabiane Oliveira da Silva; Gisele de Brito Brasil; Ivaneide Leal Ataíde Rodrigues; Laura Maria Vidal Nogueira (Universidade Federal do Paraná, 2018)
Objectives:The present study aimed to identify the importance of prenatal care for riverine pregnant women andunderstand their expectations, by discussing these aspects in order to improve the quality of the healthcare provided to this population. Method: Qualitative descriptive study that used data collected from August to October 2016, through individual interviews with 15 pregnant women who received prenatal care at the Family Health Unit of Ilha do Combú, in the south of the city of Belém, state of Pará, and analyzed with the use of thematic analysisResults:Two categories emerged from the statements of the participants. The importance of prenatal care to protect the healthofmothers and babies, and Prenatal care as a strengthand source oflearning. Conclusion:The study aimed to gain insight on the meaning of prenatal care in the lives of pregnant women, considering their particularities, make such knowledge available to health professionals, especially nurses, so that they can contribute to solve possible gaps and ensurehigh quality prenatal care.